Cloud Computing Application of Personal Information's Security in Network Sales-channels - Sun Qiong; Min Liu; Shiming Pang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With the promotion of Internet sales, the security of personal information to network users have become increasingly demanding. The existing network of sales channels has personal information security risks, vulnerable to hacker attacking. Taking full advantage of cloud security management strategy, cloud computing security management model is introduced to the network sale of personal information security applications, which is to solve the problem of information leakage. Then we proposed membership-based cloud service provided selection policy. By exploring the prospects of cloud computing in Internet sales, we try to solve the problem of the security of personal information in this channel. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3619